Analisis Kritis dan Komparatif Pendekatan Mixed-Method dalam Evaluasi Asesmen Kompetensi pada Pendidikan Teknologi dan Kejuruan Berbasis Outcome - Ali, Muttaqin Kholis; Nasution, Ichsan; Anwar, Muhammad; Simatupang, Wakhinuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The transformation towards Outcome-Based Education (OBE) requires an authentic assessment system that is capable of fully representing competency achievements, particularly in Technology and Vocational Education (TVE) which emphasises graduate work readiness. This study aims to analyse the effectiveness of the mixed-method approach in evaluating outcome-based competency assessments that cover cognitive, psychomotor, and soft skills aspects. The study used a convergent parallel mixed-method design with simultaneous quantitative and qualitative data collection. Quantitative data were obtained from 139 Year 12 Software Engineering students at a vocational school in Mandailing Natal Regency using an outcome-based assessment rubric with 30 indicators that had met construct validity and reliability. Qualitative data were collected through interviews with 21 participants consisting of students, teachers, and industry supervisors. Regression analysis results showed that psychomotor competencies and soft skills had a significant effect on students' work readiness. Thematic analysis revealed a perception gap between school and industry standards, the importance of formative feedback, and the role of work culture in competency formation. Data integration showed convergence in the aspect of adaptive problem solving, but there were still differences in collaborative competencies.